2D Tomographic Maps of Rayleigh and Love Waves for Armenia and Its Surrounding Areas - Abrehdari Seyed Hossein; Karapetyan Jon Kostikovich; Rahimi Habib; Geodakyan Eduard (Russian Journal of Earth Sciences, 2025)
This study aims to provide 2D tomography images of surface wave group velocity in Armenia and its neighboring regions within the Eurasian-Arabic plates, aiming to enhance the understanding of the shear velocity structure in the area. In this context, ∼ 516 earthquakes (M ≥ 3.5) recorded by 20 stations between 1999–2018 were analyzed, and the surface wave group velocity dispersion curves for each record (source-station path) were estimated. Subsequently, taking advantage of a 2D-linear inversion procedure, 2D tomography maps for periods of 5–80 s (Depth ≈ 180 km) were computed with a grid spacing of 0.2◦ × 0.5◦. The results of this research indicate that short-periods (5 ≤ T ≤ 25 s) are more influenced by shallow, ever-evolving deformations within various geological units, such as sedimentary basins. A minor low-velocity anomaly (Depth ≈ 27 km) is observed on the northwest slope of the Aragats volcano, which contrasts with the findings of earlier studies. For Rayleigh and Love waves, the North Armenia Block is covered by a high-velocity anomaly. The results for medium periods reveal the presence of very-high-velocity anomalies in some geological units (e.g., Lesser Caucasus), aligning with the ongoing subduction processes. In contrast, very lowvelocity anomalies reflect the uppermost mantle information, revealing an extremely thin lithosphere accompanied with a hot asthenosphere. The findings for long-periods of Love and Rayleigh waves in Armenia reveal an almost uniform velocity distribution pattern, along with very-low-velocity anomalies in the uppermost mantle, attributed to a thin lithosphere or the lack of lithospheric mantle in most units of the study region. The results demonstrate an acceptable accordance with known geological features in the Eurasian-Arabic ongoing collision zone. Overall, the main strengths of this paper lie in the application of a tomographic technique utilizing an important data set. The findings have the potential to provide new insights into the Armenian region and its surrounding areas.